CdS/CeO2/Ag2CO3 nanocomposite as an efficient heterogeneous catalyst for Knoevenagel condensation and acetylation reactions - Getachew A. Seid; Abi M. Taddesse; Neelaiah Babu; Jemal M. Yassin (Scientific Reports)
Abstract Knoevenagel condensation and acetylation reactions play a critical role in organic synthesis by facilitating the formation of carbon-carbon bonds and the modification of functional groups; however, limitations like low efficiency and demanding reaction conditions and time underscore the necessity for developing better techniques to enhance their practical applications. In this study, a ternary nanocomposite of CdS/CeO2/Ag2CO3 was synthesized by varying the molar ratio of CdS to CeO2/Ag2CO3 using the precipitation method. This heterogeneous catalyst was developed for Knoevenagel condensation and acetylation reactions applications. The optical properties, functional groups, crystalline structure, morphology, and surface area of the synthesized catalysts were characterized using UV-Vis-DRS, FTIR, XRD, SEM, and N2 adsorption-desorption isotherms, respectively. For the Knoevenagel condensation reaction between benzaldehyde and malononitrile, the optimal conditions were found to be the use of water as a solvent, at 10% w/w catalyst loading based on the total reagent mass, and room temperature (20 °C). Under these conditions, CdS/CeO2/Ag2CO3 with a CdS: CeO2/Ag2CO3 weight ratio of 3:1 gave high yields, 92.19 ± 0.41 in 33 min for Knoevenagel condensation and 93.8 ± 1.19 in just 3 min for the acetylation reaction. The reaction conditions were tested for different aromatic aldehydes with malononitrile, yielding high isolated products. The reusability of the CdS/CeO2/Ag2CO3 (3:1) catalyst was assessed, with only a 6.4% decrease in yield after sixth consecutive runs under optimal reaction conditions. Furthermore, the optimized catalyst, CdS/CeO2/Ag2CO3 (3:1), was evaluated for its catalytic activity in the acetylation of an aniline derivative. The structures of the synthesized products, 2-benzalidinemalononitrile and acetanilide, were confirmed by spectrometric techniques such as1H-NMR,13C-NMR, and FTIR analysis.